Gender Responsiveness in the Islamic Religious Education Curriculum in Islamic Elementary Schools: A Field Study Based on Paulo Freire’s Critical Pedagogy - Ferianto Ferianto; Firmansyah Firmansyah (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Gender issues are still not optimally integrated into the Islamic religious education curriculum, especially at the elementary school level, which plays an important role in shaping students' religious and social values. The Islamic religious education curriculum often reflects gender bias, both in content, pedagogical approaches, and classroom learning practices. This study aims to analyze gender responsiveness in the Islamic Religious Education curriculum in Islamic elementary schools through the lens of Paulo Freire's critical pedagogy. This study is in the field of Islamic education and critical pedagogy, which emphasizes the values of justice, dialogue, and liberation in the educational process. The method used is qualitative research based on field studies through learning observations, in-depth interviews with teachers, and analysis of curriculum documents. The results show that despite initial efforts to accommodate gender perspectives, the Islamic Religious Education curriculum is still normative and teacher-centered, thus failing to fully encourage students' critical awareness of gender justice. Paulo Freire's critical pedagogy proved relevant as an analytical framework for reconstructing a more dialogical, participatory, and reflective curriculum. This study contributes to the development of a gender-responsive Islamic Religious Education curriculum and affirms the importance of transforming it to build critical awareness and inclusive religious understanding from primary education onwards.